Strengthening the Supervision of the Free Nutritious Meal Program (MBG): Mechanisms, Challenges, and Strategic Solutions - Rodlial Ramdhan Tackbir Abubakar; Alikha Novira; Deni Fauzi Ramdani; Saekul Anwar (Publica: Jurnal Pemikiran Administrasi Negara, 2026)
The Free Nutritious Meal Program is a strategic national policy initiated by the government of the Republic of Indonesia to improve children’s nutritional status and support the development of high-quality human resources. As a large-scale public program with significant government funding and multiple stakeholders, effective supervision is essential to ensure accountability, food quality, proper distribution, and accurate beneficiary targeting. This study aims to analyze the supervisory mechanism of the MBG program, identify the challenges faced in its implementation, and propose solutions to strengthen supervisory effectiveness. This study employs a qualitative descriptive approach using in-depth interviews as the primary data collection method, supported by observation and document analysis. A total of 11 informants were selected for this study through purposive sampling, including program implementers, school representatives, beneficiaries, and supervisory actors. The collected data were analyzed using the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing. The findings indicate that the MBG program’s supervisory mechanism generally complies with the stages of management control theory, including establishing implementation standards, determining performance indicators, measuring program implementation, comparing results with established standards, and taking corrective actions. However, several challenges remain, including inconsistencies in the application of standards across regions, limited performance indicators that focus mainly on administrative aspects, weaknesses in monitoring and reporting systems, and insufficient coordination among supervising institutions. To improve the effectiveness of supervision, this study recommends strengthening operational standards, developing outcome-based performance indicators, implementing integrated digital monitoring systems, improving interagency coordination, and increasing community participation in oversight. Strengthening these aspects is expected to enhance program accountability and may help improve children’s nutritional status and support sustainable human resource development in Indonesia, although this study did not directly measure nutritional or health outcomes.